Outcome of the physiotherapy vs steroid injection in patients with trigger fingers in Hospital Tengku Ampuan Afzan (HTAA) - Su, Yuen (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Trigger finger, or stenosisng tenovaginitis, is one of the most common presentation to hand clinics. This condition arises as a result of discrepancy between the diameter of the flexor tendon and its sheath at the A1 pulley. Due to the constriction of the A1 pulley, there is “pinching” of the flexor tendon as a result of bunching-up of the fiber, which then causes formation of a nodule. At present, there are many treatment options with different success rates for trigger fingers. The purpose of this study is to compare the outcome of physiotherapy versus corticosteroid injection for the management of trigger fingers. In this single-centered, prospective randomized study, 25 patients with trigger fingers of Quinnell grade 1, 2 and 3 were randomly assigned to physiotherapy or corticosteroid injection groups. The effectiveness of the treatment was assessed by looking at the visual analogue scale, grip strength, severity of triggering and disabilities of arm, shoulder and hand (DASH) score at 6 and 12 weeks after commencement of treatment. Both groups showed statistically significant improvements in all outcome measures after treatment. Despite disease resolution at twelve weeks of treatment for both groups, corticosteroid injection group allowed earlier recovery of symptoms and improvement in our studies.